Naturhänsyn på certifierade privata skogsfastigheter : en jämförelse i praktiken mellan FSC och PEFC i Sydsverige - Andersson, Malin (SLU/Southern Swedish Forest Research Centre, 2002)
Nature conservation on certified small private forest owners- a comparison between the two certification systems FSC and PEFC in southern Sweden Today two different certification systems are used in Sweden to certify forest, FSC (Forest Stewardship Council) and PEFC (Pan European Forest Certification). During the last years certification of forests in general and different certification systems have frequently been debated. FSC is a globally widespread system and about 10 million ha out of 23 million ha Swedish forest is FSC-certified. The FSC-standard is mainly used by major forest companies and to some extent also by smaller private forest owners. PEFC is a European system and about 2 million ha Swedish forests is PEFC-certified today. The PEFC has three regional adaptations in Sweden and is mainly used by small private forest owners. The aim with this study was to compare nature conservation in FSC- and PEFC-certified forests in practice. I selected 20 small private certified estates in southern Sweden, 10 FSC and 10 PEFC. On clear-cuts were amount of created and left behind dead wood and number of large retention trees. At estate level I analysed the proportion of deciduous trees whitin a stand and the proportion of deciduous-dominated stands, spruce proportion in nemoral zone, proportion of protected forests and age distribution. The result shows that the amount of dead wood after clear-cutting was the most difficult standard variable to achieve. At average both FSC and PEFC certified estates fulfil the minimum but several owners leave too small amounts of dead wood. The number of large diameter trees left after a clear-cut is according to the standard as well as species composition, but their diameter is often small. All owners protect at least 5% of the forest area. The protected forest are not always the best available from a biodiversity point of view, a high proportion of the set-aside forests are low productive and/or situated on wet/moist ground. The result from this study show that FSC certified estates at average leaves for example more protected forest, more dead wood and more deciduous-dominated stands than PEFC. The FSC-certified forest also has a lower spruce-proportion than PEFC-certified owners. PEFC and FSC are equal when considering how many properties that reach the standards levels. From a nature protection point of view many levels in both FSC- and PEFC-standard are however low.